Diabetes Mellitus type 1: the impact on quality of life (Research, Society and Development, 2023)
Diabetes Mellitus is a chronic non-communicable pathology caused by carbohydrate metabolism disorders, the most common forms of presentation of the disease are Diabetes Mellitus Type 1 (DM1) and Type 2 (DM2), Type 1 is characterized by autoimmune disorder by interaction of genetic and environmental factors that triggers an autoimmune reaction against the β-pancreatic cells of the individual making him unable to produce insulin, this disorder appears in the first decade of life and is capable of causing acute and chronic damage to carriers. Thereby, the objective was to study the clinical aspects of DM1, and its consequences in the lives of its carriers. It was verified that the genetic bases of DM1 are related to changes in the human leukocyte antigen responsible for the non-recognition of insular antigens and tissue aggression. Due to the precocity of the symptoms, in addition to the acute repercussions (hypoglycemia and diabetic ketoacidosis), the chronic implications become important, the patients present a longer time of evolution of the pathology and of the alterations caused to the micro and macrocirculation. In DM1, microangiopathic complications are more present, however, other complications are also factors of concern and reduced quality of life and self-care. The main implications of DM1 in the life of its bearer and stress resulting from the treatment, which causes anxiety and non-acceptance of the patient.